THE IMPEDIMENTS IN CONSTRUCTION OF SUSTAINABLE BUILDINGS IN PAKISTAN - Azad, Salahuddin; Akbar, Zarmina (European Scientific Journal, ESJ, 2015)
The Concept of “Sustainable building” is the design and construction of buildings using methods and materials that are resource efficient, wellbeing of the building’s occupants, workers, health and environment friendly. Construction of Sustainable building plays an important Role in GDP of a Country and provides a wide range benefits for the society but their development suffers from different kinds of market barriers in developing countries including Pakistan. In order to find out the Impediments in Pakistan, A Survey based (Through Questionnaire) study was conducted in General Area of Rawalpindi. The Questionnaire was designed to assess the present problems faced by construction industry in Pakistan. The Response remained 63.7% and ranking of identified barriers were compared with other Asian countries. The results indicate that lack of credit resources to cover up front cost and risk of investment are one of the most important factors contributing barriers against sustainable construction. Whereas the Government support, public awareness and promotion idea of sustainable building are the recommended solution for sustainable construction.